Terminally-ill people living alone without a caregiver: an Australian national scoping study of palliative care needs - Aoun, Samar; Kristjanson, Linda; Currow, D.; Skett, K.; Oldham, Marylynn; Yates, P. (Sage Science Press (UK), 2007)
Home-based palliative care services are facing increasing challenges in servicing the needs of clients who live alone and without a primary caregiver. The findings from the analysis of 721 services’ records from three Australian states, and feedback from health professionals in interviews and postal surveys, demonstrated that there were aspects of being on one’s own with a terminal illness and living at home that require a specialised approach and support. This study explored the issues of palliative care patients living alone, from a service provider perspective, and provided evidence-based information to assist with service planning. The study made recommendations to the Australian Department of Health and Ageing about services considered important in developing support structures for this growing population.